Genetic Variability and Geographical Diversity of the Main Chagas' Disease Vector Panstrongylus megistus (Hemiptera: Triatominae) in Brazil Based on Ribosomal DNA Intergenic Sequences - Cavassin, Francelisse Bridi; Do Rocio Klisiowicz, Debora; Rodrigues Oliveira, Luiz Gustavo; Collins Kuehn, Christian; Kopp, Rogerio Luiz; Thomaz-Soccol, Vanette; Da Rosa, Joao Aristeu [UNESP]; Luz, Ennio; Mas-Coma, Santiago; Dolores Bargues, Maria (Entomological Soc Amer, 2014)
Studies were made on the ribosomal DNA intergenic region, comprising complete internal transcribed spacer (ITS)-1, 5.8S, and ITS-2 sequences, of populations of the triatomine Panstrongylus megistus, the most important vector of Chagas' disease in Brazil since Triatoma infestans eradication. Specimens were from 26 localities of Rio Grande do Sul, Santa Catarina, Parana, Sao Paulo, Minas Gerais, Bahia, and Sergipe states. In total, 21 ITS-1 and 12 ITS-2 haplotypes were found. Nucleotide differences were higher in ITS-1 (3.00%) than in ITS-2 (1.33%). The intergenic region was 1,513-1,522-bp-long (mean 1,516.9 bp), providing 26 combined haplotypes. The combination of microsatellites found in both ITSs may be of applied usefulness, to assess interpopulation specimen exchange and potential recolonizations after vector elimination by control implementation. Network results suggest that Sao Paulo may be considered one of the spreading centers of this species. Molecular clock datation suggests that P. megistus populations are diversifying at least since 4.54 million years ago, with diversification still ongoing today by geographical isolation of populations. Evidence is provided about the relationship of genetic diversity with geographical spread that characterizes a major vector and explains its ability to colonize distant areas and different ecotopes, including human habitats, and consequently its importance in Chagas' disease epidemiology.
Keywords: Panstrongylus megistus; Chagas' disease; rDNA intergenic region; haplotype diversity; Brazil